The influence of store cleanliness and POSM branding on revenue generation: learnings from a project with a major furniture brand - Shafat, K.M. Asif Muznabeen (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.